Thermoplastic resin composition and molded article manufactured therefrom
By introducing specific components and structures into the thermoplastic resin, the impact resistance, weather resistance, heat resistance and coloring properties of the resin are improved, and the shortcomings of existing resins in applications of high gloss and high appearance characteristics are solved.
Patent Information
- Application Number
- CN202380057543.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-07-29
- Filing Date
- 2023-07-26
- Publication Date
- 2025-04-11
AI Technical Summary
Existing thermoplastic resins, such as ASA resins and ASA/PMMA alloy resins, have problems of deterioration in color properties, insufficient impact resistance and heat resistance, especially in applications requiring high gloss and high appearance characteristics.
The thermoplastic resin composition is adopted, including a silicone-acrylate composite rubber modified graft copolymer, acrylic rubber modified graft copolymer, α-methylstyrene copolymer, polyalkyl (meth)acrylate resin and high molecular weight aromatic vinyl-vinyl cyano copolymer, and the impact resistance, weather resistance, heat resistance and coloring properties of the resin are improved by adjusting the proportion and structure of these components.
The excellent impact resistance, weather resistance, heat resistance, colorability and appearance characteristics of the thermoplastic resin composition and its molded products are achieved, and the application needs of high gloss and high appearance characteristics are met.
Smart Images

Figure BDA0005260139900000091 
Figure BDA0005260139900000101 
Figure BDA0005260139900000111
Abstract
Description
Technical Field
[0001] The present invention relates to a thermoplastic resin composition and a molded article produced therefrom. Background Art
[0002] In line with the recent environmentally friendly trend and the need for cost reduction, the demand for unpainted thermoplastic resins that can be used without a painting process is increasing. Unpainted thermoplastic resins (molded products thereof are used directly without painting) are required to have excellent scratch resistance, colorability, impact resistance, weather resistance, etc. Accordingly, acrylonitrile-styrene-acrylate copolymer resins (hereinafter referred to as ASA resins) having overall excellent impact resistance, heat resistance and weather resistance are representatively used as unpainted thermoplastic resins.
[0003] However, ASA resins have problems in that colorability is deteriorated due to differences in refractive index between components constituting the ASA resin and differences in particle size of the rubbery polymer component during use, and also have limitations in that it is difficult to apply to parts requiring high gloss.
[0004] Accordingly, more and more people try to mix ASA resin with polymethyl methacrylate resin (hereinafter, PMMA resin) so as to apply ASA / PMMA alloy resin to applications requiring high appearance characteristics, but ASA / PMMA alloy resin has the disadvantage that impact resistance and heat resistance are inferior to ASA resin. In order to improve the heat resistance of ASA / PMMA alloy resin, a heat resistance enhancer can be used, but due to the difference in refractive index between the continuous phase (matrix) and the dispersed phase (domain), the heat resistance enhancer deteriorates the transparency and colorability of the molded product, and in order to color the molded product, it may be necessary to use an excessive amount of colorant, such as pigment, dye, etc.
[0005] Accordingly, there is a need to develop thermoplastic resin compositions having excellent impact resistance, weather resistance, heat resistance, colorability, and the like. Summary of the invention
[0006]
Technical issues
[0007] Embodiments provide a thermoplastic resin composition having excellent impact resistance, weather resistance, heat resistance, colorability, and appearance characteristics, and a molded article made therefrom.
[0008]
Technical solution
[0009] According to an embodiment, a thermoplastic resin composition includes 100 parts by weight of a base resin including: (A) 5 to 20 wt% of a silicone-acrylate composite rubber-modified graft copolymer; (B) 15 to 25 wt% of an acrylic rubber-modified graft copolymer having a rubber-like polymer with an average particle size of 100 to 200 nm; (C) 10 to 15 wt% of an acrylic rubber-modified graft copolymer having a rubber-like polymer with an average particle size of 300 to 400 nm; (D) 40 to 60 wt% of an α-methylstyrene copolymer; and (E) 5 to 15 wt% of a polyalkyl (meth)acrylate resin, and (F) 1 to 5 parts by weight of an aromatic vinyl-vinyl cyanide copolymer having a weight average molecular weight greater than or equal to 5,000,000 g / mol based on the above base resin, wherein the weight ratio of (A) + (B): (C) is 4:1 to 1:1 and the weight ratio of (A): (B) is 1:0.5 to 1:5.
[0010] (A) The silicone-acrylate composite rubber-modified graft copolymer may include a core comprising a silicone-acrylate composite rubber-like polymer, and a shell formed by graft-polymerizing at least one selected from a (meth)acrylate compound, an aromatic vinyl compound, and a vinyl cyanide compound onto the core.
[0011] The average particle size of the silicone-acrylate composite rubber-like polymer may be 100 to 200 nm.
[0012] (A) The silicone-acrylate composite rubber-modified graft copolymer may include an acrylate-silicone cross-linked copolymer core, and a shell formed by grafting a styrene-acrylonitrile (SAN) copolymer onto the core.
[0013] (B) an acrylic rubber-modified graft copolymer of a rubber-like polymer having an average particle size of 100 to 200 nm and (C) an acrylic rubber-modified graft copolymer of a rubber-like polymer having an average particle size of 300 to 400 nm may each include a core comprising an acrylic rubber-like polymer, and a shell formed by graft-polymerizing at least one selected from a (meth)acrylate compound, an aromatic vinyl compound and a vinyl cyanide compound onto the core.
[0014] The cores of the acrylic rubber-like polymer of (B) the acrylic rubber-modified graft copolymer of the rubber-like polymer having an average particle size of 100 to 200 nm and (C) the acrylic rubber-modified graft copolymer of the rubber-like polymer having an average particle size of 300 to 400 nm may each include a butyl acrylate-styrene crosslinked copolymer core, and a shell formed by grafting a styrene-acrylonitrile (SAN) copolymer onto the core.
[0015] (D) The α-methylstyrene-based copolymer may be a copolymer of a monomer mixture including 40 to 75 wt % of α-methylstyrene, 15 to 35 wt % of an aromatic vinyl compound, and 10 to 30 wt % of a vinyl cyanide compound.
[0016] (D) The α-methylstyrene-based copolymer may be an α-methylstyrene-styrene-acrylonitrile copolymer.
[0017] (E) The polyalkyl (meth)acrylate resin may be a polymethyl methacrylate (PMMA) resin.
[0018] (F) The aromatic vinyl-vinyl cyanide copolymer having a weight average molecular weight of greater than or equal to 5,000,000 g / mol may be a styrene-acrylonitrile copolymer having a weight average molecular weight of greater than or equal to 5,000,000 g / mol.
[0019] The thermoplastic resin composition may further include at least one additive selected from the group consisting of flame retardants, nucleating agents, coupling agents, fillers, plasticizers, lubricants, mold release agents, heat stabilizers, antioxidants, ultraviolet (UV) stabilizers, pigments, and dyes.
[0020] In another embodiment, a molded article made from the thermoplastic resin composition is provided.
[0021] The molded article has an Izod impact strength s greater than or equal to 7 kgf·cm / cm as measured on a 1 / 8 inch thick sample according to ASTM D256 standard.
[0022] The molded article may have a Vicat softening temperature (VST) greater than or equal to 101° C., measured under B50 conditions according to ISO 306 standard.
[0023] The molded article may have a color change (ΔE) of less than or equal to 3.0 before and after a weathering test as measured by irradiating the molded article with an energy of 4,500 kJ according to the SAE J 1960 standard.
[0024]
Beneficial Effects
[0025] A thermoplastic resin composition having excellent impact resistance, weather resistance, heat resistance, colorability and appearance characteristics, and a molded article produced therefrom can be provided. DETAILED DESCRIPTION
[0026] Hereinafter, embodiments of the present invention are described in detail. However, these embodiments are exemplary, and the present disclosure is not limited thereto.
[0027] In the present specification, unless otherwise mentioned, "copolymerization" means block copolymerization, random copolymerization or graft copolymerization, and "copolymer" means block copolymer, random copolymer or graft copolymer.
[0028] In the present specification, unless otherwise mentioned, the average particle size of the rubbery polymer refers to a volume average diameter, and means a Z-average particle size measured using a dynamic light scattering analysis instrument.
[0029] In this specification, unless otherwise mentioned, the weight average molecular weight is measured by dissolving a powder sample in an appropriate solvent and then subjecting it to gel permeation chromatography (GPC) using 1200 series manufactured by Agilent Technologies (the standard sample is polystyrene manufactured by Shodex).
[0030] According to an embodiment, the thermoplastic resin composition includes 100 parts by weight of a base resin including: (A) 5 to 20 wt% of a silicone-acrylate composite rubber-modified graft copolymer; (B) 15 to 25 wt% of an acrylic rubber-modified graft copolymer having a rubber-like polymer with an average particle size of 100 to 200 nm; (C) 10 to 15 wt% of an acrylic rubber-modified graft copolymer having a rubber-like polymer with an average particle size of 300 to 400 nm; (D) 40 to 60 wt% of an α-methylstyrene copolymer; and (E) 5 to 15 wt% of a polyalkyl (meth)acrylate resin, and (F) 1 to 5 parts by weight of an aromatic vinyl-vinyl cyanide copolymer having a weight average molecular weight greater than or equal to 5,000,000 g / mol based on the above base resin, wherein the weight ratio of (A) + (B): (C) is 4:1 to 1:1, and the weight ratio of (A): (B) is 1:0.5 to 1:5.
[0031] Hereinafter, each component included in the thermoplastic resin composition will be described in detail.
[0032] (A) Silicone-acrylate composite rubber modified graft copolymer
[0033] In an embodiment, the (A) silicone-acrylate composite rubber-modified graft copolymer imparts excellent impact resistance to the thermoplastic resin composition. The (A) silicone-acrylate composite rubber-modified graft copolymer may include a core including a silicone-acrylate composite rubber-like polymer, and a shell formed by graft-polymerizing at least one selected from a (meth)acrylate compound, an aromatic vinyl compound, and a vinyl cyanide compound onto the core.
[0034] (A) The silicone-acrylate composite rubber-modified graft copolymer can be prepared by using emulsion polymerization, suspension polymerization, solution polymerization, bulk polymerization, etc., and can be prepared, for example, by the following method (but not limited thereto): preparing a silicone-acrylate composite rubber-like polymer, and graft-polymerizing a monomer mixture including at least one selected from a (meth)acrylate compound, an aromatic vinyl compound, and a vinyl cyanide compound onto a core formed by at least one layer of the above-mentioned silicone-acrylate composite rubber-like polymer to form at least one layer of a shell.
[0035] The silicone-acrylate composite rubbery polymer may be a cross-linked copolymer of an acrylate compound-silicone compound, or a mixture of an acrylic rubbery polymer and a silicone rubbery polymer.
[0036] The acrylic rubber-like polymer may be a cross-linked polymer prepared by using an acrylic ester compound as a main monomer. The acrylic ester compound may be, for example, ethyl acrylate, butyl acrylate, 2-ethylhexyl acrylate, hexyl acrylate, or a combination thereof, but is not limited thereto.
[0037] The silicone-based rubber-like polymer may be a cross-linked polymer prepared by using a silicone-based compound as a main monomer. The silicone-based compound may be, for example, dimethylsiloxane, methylphenylsiloxane, methylvinylsiloxane, or a combination thereof, but is not limited thereto.
[0038] The average particle size of the silicone-acrylate composite rubber-like polymer may be 100 to 200 nm, for example, 120 to 180 nm. Within the above average particle size range, the thermoplastic resin composition may have improved impact resistance and colorability.
[0039] In the silicone-acrylate composite rubbery polymer, a weight ratio of the component derived from the acrylate compound to the component derived from the silicone compound may be 95:5 to 85:15, for example 95:5 to 90:10. Within this range, the thermoplastic resin composition may have improved impact resistance and colorability.
[0040] The silicone-acrylate composite rubber-like polymer may be included in an amount of 20 to 60 wt %, such as 30 to 60 wt %, such as 40 to 60 wt %, based on 100 wt % of the (A) silicone-acrylate composite rubber-modified graft copolymer.
[0041] The (meth)acrylate compound included in the shell may be at least one selected from methacrylate, acrylate, methyl methacrylate, methyl acrylate, ethyl methacrylate, ethyl acrylate, propyl methacrylate, propyl acrylate, butyl methacrylate and butyl acrylate, but is not limited thereto.
[0042] The aromatic vinyl compound included in the shell may be at least one selected from the group consisting of styrene, α-methylstyrene, p-methylstyrene, p-tert-butylstyrene, 2,4-dimethylstyrene, chlorostyrene, vinyltoluene, and vinylnaphthalene, but is not limited thereto.
[0043] The vinyl cyanide compound included in the shell may be at least one selected from the group consisting of acrylonitrile, methacrylonitrile, and fumaronitrile, but is not limited thereto.
[0044] In an embodiment, when a monomer mixture including an aromatic vinyl compound and a vinyl cyanide compound is graft-polymerized onto a silicone-acrylate composite rubbery polymer to form a shell, the shell may be a copolymer of a monomer mixture including an aromatic vinyl compound and a vinyl cyanide compound in a weight ratio of 1:1 to 4:1 (e.g., 1:1 to 3:1).
[0045] In an embodiment, the (A) silicone-acrylate composite rubber modified graft copolymer may include a core of a crosslinked copolymer of an acrylate-silicone compound, and a shell formed by grafting a styrene-acrylonitrile (SAN) copolymer onto the core.
[0046] In an embodiment, based on 100wt% of the base resin, the content of the (A) silicone-acrylate composite rubber-modified graft copolymer may be greater than or equal to 5wt%, such as greater than or equal to 10wt%, such as greater than or equal to 15wt%, and such as less than or equal to 20wt%, such as less than or equal to 15wt%, such as less than or equal to 10wt%, such as 5-20wt%, such as 5-15wt%, such as 5-10wt%. Within the above weight range, the thermoplastic resin composition may have excellent impact resistance, fluidity and colorability.
[0047] (B) Acrylic rubber modified with a rubbery polymer having a core-shell structure and an average particle size of 100 to 200 nm and (C) a propylene copolymer having a core-shell structure and a rubbery polymer having an average particle size of 300 to 400 nm. Acids Rubber modified graft copolymers.
[0048] The thermoplastic resin composition according to the embodiment includes (B) an acrylic rubber-modified graft copolymer having a core-shell structure of a rubber-like polymer with an average particle size of 100 to 200 nm, and (C) an acrylic rubber-modified graft copolymer having a core-shell structure of a rubber-like polymer with an average particle size of 300 to 400 nm, wherein the average particle sizes of the rubber-like polymers are different from each other. The acrylic rubber-modified graft copolymers of (B) and (C) above play a role in enhancing various physical properties (such as impact resistance, mechanical properties, and appearance properties) of the thermoplastic resin composition.
[0049] In an embodiment, (B) an acrylic rubber-modified graft copolymer having a rubbery polymer with an average particle size of 100 to 200 nm and (C) an acrylic rubber-modified graft copolymer having a rubbery polymer with an average particle size of 300 to 400 nm may have other properties that are the same as or different from each other except for the average particle size of the rubbery polymer.
[0050] In an embodiment, (B) an acrylic rubber-modified graft copolymer of a rubber-like polymer having an average particle size of 100 to 200 nm and (C) an acrylic rubber-modified graft copolymer of a rubber-like polymer having an average particle size of 300 to 400 nm may each include an acrylic rubber-like polymer core and a shell formed by graft-polymerizing at least one selected from a (meth)acrylate compound, an aromatic vinyl compound, and a vinyl cyanide compound onto the core.
[0051] (B) the acrylic rubber-modified graft copolymer of the rubbery polymer having an average particle size of 100 to 200 nm and (C) the acrylic rubber-modified graft copolymer of the rubbery polymer having an average particle size of 300 to 400 nm can each be prepared by any preparation method known to those skilled in the art.
[0052] As for the preparation method, conventional polymerization methods (such as emulsion polymerization, suspension polymerization, solution polymerization and bulk polymerization) can be used. As a non-limiting example, it can be prepared by the following method: preparing an acrylic rubber-like polymer, and graft-polymerizing at least one selected from (meth) acrylic acid ester compounds, aromatic vinyl compounds and vinyl cyanide compounds onto a core formed of at least one layer of the above acrylic rubber-like polymer to form at least one layer of shell.
[0053] The acrylic rubber-like polymer may be a cross-linked polymer prepared using an acrylic ester compound as a main monomer. The acrylic ester compound may be, for example, ethyl acrylate, butyl acrylate, 2-ethylhexyl acrylate, hexyl acrylate, or a combination thereof.
[0054] The acrylic monomers may be copolymerized with one or more other free radical polymerizable monomers. When copolymerized, the amount of the one or more other free radical polymerizable monomers may be 5 to 30 wt%, such as 10 to 20 wt%, based on the total weight of the acrylic rubber polymer.
[0055] In an embodiment, the (meth)acrylate compound included in the shell may be at least one selected from methacrylate, acrylate, methyl methacrylate, methyl acrylate, ethyl methacrylate, ethyl acrylate, propyl methacrylate, propyl acrylate, butyl methacrylate, and butyl acrylate, but is not limited thereto.
[0056] The aromatic vinyl compound included in the shell may be at least one selected from the group consisting of styrene, α-methylstyrene, p-methylstyrene, p-tert-butylstyrene, 2,4-dimethylstyrene, chlorostyrene, vinyltoluene, and vinylnaphthalene, but is not limited thereto.
[0057] The vinyl cyanide compound included in the shell may be at least one selected from the group consisting of acrylonitrile, methacrylonitrile, and fumaronitrile, but is not limited thereto.
[0058] In an embodiment, when a monomer mixture including an aromatic vinyl compound and a vinyl cyanide compound is graft-polymerized onto a core including an acrylic rubber-like polymer to form a shell, the shell may be a copolymer including a monomer mixture of an aromatic vinyl compound and a vinyl cyanide compound in a weight ratio of 1:1 to 4:1 (e.g., 1:1 to 3:1).
[0059] In an embodiment, the core of the acrylic rubber-like polymer of (B) the acrylic rubber-modified graft copolymer of the rubber-like polymer having an average particle size of 100 to 200 nm and (C) the acrylic rubber-modified graft copolymer of the rubber-like polymer having an average particle size of 300 to 400 nm may each include a butyl acrylate-styrene cross-linked copolymer core, and a shell formed by grafting a styrene-acrylonitrile (SAN) copolymer onto the core.
[0060] In an embodiment, the content of (B) the acrylic rubber-modified graft copolymer having a rubber-like polymer with an average particle size of 100 to 200 nm may be 15 to 25 wt%, such as 15 to 20 wt%, such as 20 to 25 wt%, based on 100 wt% of the base resin. Within the above wt% range, the impact resistance of the thermoplastic resin composition may be improved.
[0061] In an embodiment, the content of (C) the acrylic rubber-modified graft copolymer having a rubber-like polymer with an average particle size of 300-400 nm may be 10-15 wt % based on 100 wt % of the base resin. Within the above wt % range, the impact resistance of the thermoplastic resin composition may be improved.
[0062] In an embodiment, among the components, the weight ratio of component (A) + (B): (C) may be 4: 1 to 1: 1, for example, 4: 1 to 1.5: 1, and the weight ratio of component (A): (B) may be 1: 0.5 to 1: 5, for example, 1: 1 to 1: 5. Within the above weight ratio range, the impact resistance, colorability and appearance characteristics of the thermoplastic resin composition and the molded article made therefrom can be further improved.
[0063] (D) Alpha-methylstyrene (α-methylstyrene) copolymers
[0064] In an embodiment, the (D) α-methylstyrene-based copolymer may improve heat resistance of the thermoplastic resin composition.
[0065] (D) The α-methylstyrene-based copolymer can be prepared using a conventional production method such as emulsion polymerization, suspension polymerization, solution polymerization, and bulk polymerization.
[0066] In an embodiment, (D) the α-methylstyrene copolymer may be a copolymer of a monomer mixture including 40 to 75 wt% of α-methylstyrene, 15 to 35 wt% of an aromatic vinyl compound, and 10 to 30 wt% of a vinyl cyanide compound. Within the above weight range, the thermoplastic resin composition may have excellent heat resistance and impact resistance.
[0067] In (D) α-methylstyrene copolymers, the aromatic vinyl compound may be selected from styrene (except α-methylstyrene) substituted or unsubstituted by halogen or C1-C10 alkyl groups and combinations thereof, and the vinyl cyanide compound may be selected from acrylonitrile, methacrylonitrile, fumaronitrile and combinations thereof.
[0068] In an embodiment, the (D) α-methylstyrene-based copolymer may be an α-methylstyrene-styrene-acrylonitrile copolymer.
[0069] The (D) α-methylstyrene-based copolymer may have a weight average molecular weight of 50,000 to 300,000 g / mol, for example, 100,000 to 200,000 g / mol. When the above range is satisfied, a thermoplastic resin composition including the same may exhibit excellent impact resistance and fluidity.
[0070] Based on 100wt% of the base resin, the content of (D) α-methylstyrene copolymer may be greater than or equal to 40wt%, for example, greater than or equal to 45wt%, for example, greater than or equal to 50wt%, for example, greater than or equal to 55wt%, and the content may be less than or equal to 60wt%, for example, less than or equal to 55wt%, for example, less than or equal to 50wt%, for example, less than or equal to 45wt%, and the content may be 40-60wt%, for example, 50-60wt%. Within the above weight range, the thermoplastic resin composition may have excellent heat resistance, fluidity and impact resistance.
[0071] (E) Polyalkyl (meth)acrylate resin
[0072] The thermoplastic resin composition according to an embodiment includes (E) a polyalkyl (meth)acrylate resin, wherein the (E) polyalkyl (meth)acrylate resin may improve colorability and weather resistance of the thermoplastic resin composition.
[0073] (E) The polyalkyl (meth)acrylate resin can be obtained by polymerizing an alkyl (meth)acrylate compound by a known polymerization method such as suspension polymerization, bulk polymerization or emulsion polymerization.
[0074] The alkyl (meth)acrylate-based compound may be at least one selected from methyl methacrylate, methyl acrylate, ethyl methacrylate, ethyl acrylate, propyl methacrylate, propyl acrylate, butyl methacrylate, and butyl acrylate, but is not limited thereto.
[0075] The glass transition temperature of the (E) polyalkyl (meth)acrylate resin may be 100 to 150°C, for example, 110 to 130°C.
[0076] The (E) polyalkyl (meth)acrylate resin may have a weight average molecular weight of 50,000 to 200,000 g / mol, for example, 70,000 to 150,000 g / mol. When the above range is satisfied, the thermoplastic resin composition may exhibit excellent scratch resistance and processability.
[0077] In embodiments, the (E) polyalkyl(meth)acrylate resin may be a polymethyl methacrylate (PMMA) resin.
[0078] The (E) polyalkyl (meth)acrylate resin may be included in an amount of 5 to 15 wt %, such as 5 to 10 wt %, such as 10 to 15 wt %, based on 100 wt % of the base resin. Within the above weight range, the thermoplastic resin composition may have excellent colorability and weather resistance.
[0079] (F) an aromatic vinyl-vinyl cyanide copolymer having a weight average molecular weight greater than or equal to 5,000,000 g / mol thing
[0080] In an embodiment, (F) an aromatic vinyl-vinyl cyanide copolymer having a weight average molecular weight of greater than or equal to 5,000,000 g / mol is used to improve the appearance characteristics of the thermoplastic resin composition.
[0081] (F) The weight average molecular weight of the aromatic vinyl-vinyl cyanide copolymer having a weight average molecular weight greater than or equal to 5,000,000 g / mol may be greater than or equal to 5,000,000 g / mol, for example, 5,000,000 to 10,000,000 g / mol, for example, 5,000,000 to 9,000,000 g / mol, for example, 5,000,000 to 8,000,000 g / mol, for example, 5,000,000 to 7,000,000 g / mol.
[0082] In embodiments, (F) the aromatic vinyl-vinyl cyanide copolymer having a weight average molecular weight greater than or equal to 5,000,000 g / mol may be a styrene-acrylonitrile copolymer having a weight average molecular weight greater than or equal to 5,000,000 g / mol.
[0083] According to an embodiment, the content of (F) an aromatic vinyl-vinyl cyanide copolymer having a weight average molecular weight of greater than or equal to 5,000,000 g / mol may be, for example, 1 to 5 parts by weight, for example, 1 to 3 parts by weight, based on 100 parts by weight of the base resin. Within the above weight range, the thermoplastic resin composition and the molded article made therefrom may have excellent appearance characteristics because the occurrence of flow marks is suppressed.
[0084] (G) Additives
[0085] In addition to components (A) to (F), the thermoplastic resin composition according to an embodiment may further include one or more additives necessary to achieve a balance between properties while exhibiting excellent impact resistance, heat resistance, weather resistance, and colorability or depending on the final use of the thermoplastic resin composition.
[0086] Specifically, the additive may further include at least one additive selected from flame retardants, nucleating agents, coupling agents, fillers, plasticizers, lubricants, mold release agents, thermal stabilizers, antioxidants, ultraviolet (UV) stabilizers, dyes, and pigments.
[0087] These additives may be appropriately included unless the characteristics of the thermoplastic resin composition are deteriorated, and specifically, the content of these additives is less than or equal to about 20 parts by weight based on 100 parts by weight of the base resin, but is not limited thereto.
[0088] On the other hand, the thermoplastic resin composition of the embodiment may be mixed with other resins or other rubber components.
[0089] On the other hand, another embodiment provides a molded article manufactured using the thermoplastic resin composition according to the embodiment. The molded article can be manufactured by various methods known in the related art (for example, by injection molding, extrusion molding, etc. using the thermoplastic resin composition).
[0090] The molded article has an Izod impact strength of greater than or equal to 7 kgf·cm / cm, greater than or equal to 8 kgf·cm / cm, greater than or equal to 9 kgf·cm / cm, or greater than or equal to 10 kgf·cm / cm, measured on a 1 / 8 inch thick sample according to ASTM D256.
[0091] The molded article may have a Vicat softening temperature (VST) greater than or equal to 101° C., greater than or equal to 102° C., or greater than or equal to 103° C., measured under B50 conditions according to ISO 306 standard.
[0092] The molded article may have a color change (ΔE) of less than or equal to 3.0, less than or equal to 2.9, less than or equal to 2.8, less than or equal to 2.7, less than or equal to 2.6, less than or equal to 2.5, less than or equal to 2.4, less than or equal to 2.3, less than or equal to 2.2, less than or equal to 2.1, or less than or equal to 2.0 before and after the weathering test, as measured by irradiating the molded article with 4,500 kJ of energy according to the SAE J 1960 standard.
[0093]
Invention Mode
[0094] Hereinafter, preferred embodiments of the present invention will be described. However, these embodiments are not to be construed as limiting the scope of the present invention in any case.
[0095] Examples 1 to 4 and Comparative Examples 1 to 6
[0096] According to the content ratio of each component shown in Table 1, thermoplastic resin compositions according to Examples 1 to 4 and Comparative Examples 1 to 6 were prepared, respectively.
[0097] Based on the total weight of 100 parts by weight of components (A) to (E), the components shown in Table 1 are dry-mixed with 0.5 parts by weight of a quinone dye mixture showing black, and then, melted / kneaded by quantitatively and continuously feeding the mixture into the feed section of a twin-screw extruder (L / D=29, Φ=45mm). In this article, the barrel temperature of the twin-screw extruder is set to about 240°C. Subsequently, the pellets of the thermoplastic resin composition obtained by the twin-screw extruder are dried at about 80°C for about 4 hours, and then, a sample for measuring physical properties is made by using a 6-ounce injection molding machine set to a cylinder temperature of about 240°C and a mold temperature of about 60°C. The measured properties are shown in Table 2.
[0098] In Table 1, components (A) to (E) are expressed as wt% based on the total weight of components (A) to (E), and component (F) is expressed as parts by weight based on 100 parts by weight of the total weight of components (A) to (E).
[0099] (Table 1)
[0100]
[0101]
[0102] Each component listed in Table 1 is described in detail below.
[0103] (A) Silicone-acrylate composite rubber modified graft copolymer
[0104] Use core-shell graft copolymer (product name: Metablen TM SX-006, manufacturer: Mitsubishi Chemical Corporation), which includes about 60 wt % of a core including an acrylate-silicone crosslinked copolymer and having an average particle size of about 150 nm and a shell formed by grafting styrene and acrylonitrile to the core at a weight ratio of about 2:1.
[0105] (B) Acrylic rubber-modified graft copolymer having a rubbery polymer with an average particle size of 100 to 200 nm
[0106] A core-shell copolymer (manufacturer: Lotte Chemical Co., Ltd.) was used, which included a core of about 50 wt % including a butyl acrylate-styrene crosslinked copolymer and having an average particle size of about 130 nm and a shell formed by grafting a styrene-acrylonitrile copolymer (styrene:acrylonitrile=about 7:3 weight ratio) onto the core.
[0107] (C) Acrylic rubber-modified graft copolymer having a rubbery polymer with an average particle size of 300 to 400 nm
[0108] A core-shell copolymer (manufacturer: Lotte Chemical Co., Ltd.) was used, which included a core of about 50 wt % including a butyl acrylate-styrene crosslinked copolymer and having an average particle size of about 380 nm and a shell formed by grafting a styrene-acrylonitrile copolymer (styrene:acrylonitrile=about 7:3 weight ratio) onto the core.
[0109] (D-1) α-Methylstyrene copolymer
[0110] An α-methylstyrene-styrene-acrylonitrile copolymer (manufacturer: Lotte Chemical Co., Ltd.) having a weight average molecular weight of about 160,000 g / mol obtained by copolymerizing a monomer mixture including about 54 wt % of α-methylstyrene, about 30 wt % of styrene and about 16 wt % of acrylonitrile was used.
[0111] (D-2) Styrene copolymer
[0112] A styrene-acrylonitrile copolymer (manufacturer: Lotte Chemical Co., Ltd.) having a weight average molecular weight of about 110,000 g / mol, which was obtained by copolymerizing a monomer mixture of about 71 wt % of styrene and about 29 wt % of acrylonitrile, was used.
[0113] (E) Polyalkyl (meth)acrylate resin
[0114] A polymethyl methacrylate resin (manufacturer: Lotte Chemical Co., Ltd.) having a weight average molecular weight of 100,000 g / mol was used.
[0115] (F) an aromatic vinyl-vinyl cyanide copolymer having a weight average molecular weight of greater than or equal to 5,000,000 g / mol
[0116] A styrene-acrylonitrile copolymer having a weight average molecular weight greater than or equal to 5,000,000 g / mol (product name: ZB869, manufacturer: Zibo Huaxing Auxiliary Agent Co., Ltd.) was used.
[0117] Characteristic evaluation
[0118] The impact resistance, coloring, heat resistance, appearance characteristics, and weather resistance of the samples for measuring physical properties according to Examples 1 to 4 and Comparative Examples 1 to 6 were measured in the following methods, and the evaluation results are shown in Table 2.
[0119] (1) Impact resistance (unit: kgf·cm / cm): Izod impact strength was measured using a 1 / 8 inch thick notched specimen in accordance with ASTM D256.
[0120] (2) Colorability: Lightness (L*) was measured in the specular exclusion (SCE) mode using a 2.5 mm thick sample using CM-3700d manufactured by Konica Minolta Co., Ltd. The lower the lightness, the better the black color was achieved, which was judged to exhibit excellent colorability.
[0121] (3) Heat resistance (unit: °C): Vicat softening temperature (VST) was measured under B50 condition according to ISO 306.
[0122] (4) Appearance characteristics: Samples with a size of 90 mm × 50 mm × 2 mm, which were high-speed injection molded using a mold with a point gate structure, were used to inspect the extent of flow marks with the naked eye, and the flow marks were classified into ○ (appeared, clearly visible), △ (appeared, somewhat blurred), and X (not appeared).
[0123] (5) Weatherability: The color change (ΔE) was measured using a CM-3700d manufactured by Konica Minolta in the specular reflection exclusion (SCE) mode. The color change was measured using an ATLAS Ci4000 Xenon-arc accelerated weathering tester in accordance with ISO 4892 and evaluated before and after 1500 hours under accelerated weathering conditions.
[0124] (Table 2)
[0125]
[0126] Referring to the results of Tables 1 to 2, it was confirmed that the thermoplastic resin composition including components (A) to (F) and the molded article produced therefrom exhibited all excellent impact resistance, colorability, heat resistance, weather resistance and appearance characteristics.
[0127] While the invention has been described in connection with what are presently considered to be practical example embodiments, it is to be understood that the invention is not limited to the disclosed embodiments. On the contrary, the invention is intended to cover various modifications and equivalent arrangements included within the spirit and scope of the appended claims.
Claims
1. A thermoplastic resin composition comprising 100 parts by weight of the base resin comprising the following: (A) 5 to 20 wt% of a silicone-acrylate composite rubber-modified graft copolymer; (B) 15 to 25 wt% of an acrylic rubber-modified graft copolymer of a rubbery polymer having an average particle size of 100 to 200 nm; (C) 10 to 15 wt % of an acrylic rubber-modified graft copolymer of a rubbery polymer having an average particle size of 300 to 400 nm; (D) 40 to 60 wt% of an α-methylstyrene copolymer; and (E) 5 to 15 wt% of a polyalkyl (meth)acrylate resin, and (F) 1 to 5 parts by weight of an aromatic vinyl-vinyl cyanide copolymer having a weight average molecular weight greater than or equal to 5,000,000 g / mol based on the above base resin, wherein the weight ratio of (A)+(B):(C) is 4:1 to 1:1, and The weight ratio of (A):(B) is 1:0.5 to 1:
5.
2. The thermoplastic resin composition according to claim 1, wherein (A) The silicone-acrylate composite rubber-modified graft copolymer includes a core comprising a silicone-acrylate composite rubber-like polymer, and a shell formed by graft-polymerizing at least one selected from a (meth)acrylate compound, an aromatic vinyl compound, and a vinyl cyanide compound onto the core.
3. The thermoplastic resin composition according to claim 2, wherein The average particle size of the silicone-acrylate composite rubber-like polymer is 100-200 nm.
4. The thermoplastic resin composition according to any one of claims 1 to 3, wherein (A) The silicone-acrylate composite rubber-modified graft copolymer includes an acrylate-silicone cross-linked copolymer core, and a shell formed by grafting a styrene-acrylonitrile (SAN) copolymer onto the core.
5. The thermoplastic resin composition according to any one of claims 1 to 4, wherein The (B) acrylic rubber-modified graft copolymer of a rubber-like polymer having an average particle size of 100 to 200 nm and the (C) acrylic rubber-modified graft copolymer of a rubber-like polymer having an average particle size of 300 to 400 nm each include a core comprising an acrylic rubber-like polymer, and a shell formed by graft-polymerizing at least one selected from a (meth)acrylic acid ester compound, an aromatic vinyl compound and a vinyl cyanide compound onto the core.
6. The thermoplastic resin composition according to any one of claims 1 to 5, wherein The cores of the acrylic rubber-like polymer of (B) the acrylic rubber-modified graft copolymer of the rubber-like polymer having an average particle size of 100 to 200 nm and (C) the acrylic rubber-modified graft copolymer of the rubber-like polymer having an average particle size of 300 to 400 nm each include a butyl acrylate-styrene crosslinked copolymer core and a shell formed by grafting a styrene-acrylonitrile (SAN) copolymer onto the core.
7. The thermoplastic resin composition according to any one of claims 1 to 6, wherein (D) The α-methylstyrene-based copolymer is a copolymer of a monomer mixture including 40 to 75 wt% of α-methylstyrene, 15 to 35 wt% of an aromatic vinyl compound, and 10 to 30 wt% of a vinyl cyanide compound.
8. The thermoplastic resin composition according to any one of claims 1 to 7, wherein (D) The α-methylstyrene copolymer is an α-methylstyrene-styrene-acrylonitrile copolymer.
9. The thermoplastic resin composition according to any one of claims 1 to 8, wherein (E) The polyalkyl (meth)acrylate resin is a polymethyl methacrylate (PMMA) resin.
10. The thermoplastic resin composition according to any one of claims 1 to 9, wherein (F) The aromatic vinyl-vinyl cyanide copolymer having a weight average molecular weight of 5,000,000 g / mol or more is a styrene-acrylonitrile copolymer having a weight average molecular weight of 5,000,000 g / mol or more.
11. The thermoplastic resin composition according to any one of claims 1 to 10, wherein The thermoplastic resin composition further includes at least one additive selected from the group consisting of flame retardants, nucleating agents, coupling agents, fillers, plasticizers, lubricants, mold release agents, thermal stabilizers, antioxidants, ultraviolet (UV) stabilizers, dyes, and pigments.
12. A molded product produced from the thermoplastic resin composition according to any one of claims 1 to 11.
13. The molded article according to claim 12, wherein The molded article has an Izod impact strength of greater than or equal to 7 kgf·cm / cm as measured on a 1 / 8 inch thick sample according to ASTM D256 standard.
14. The molded article of claim 12 or claim 13, wherein The molded article has a Vicat softening temperature (VST) greater than or equal to 101° C., measured under B50 conditions according to ISO 306 standard.
15. The molded article according to any one of claims 12 to 14, wherein The molded article has a color change (ΔE) of less than or equal to 3.0 before and after weathering evaluation as measured by irradiating the molded article with an energy of 4,500 kJ according to SAE J 1960.